Atomic layer etching of silicon nitride using cyclic process with hydrofluorocarbon chemistry. (30th May 2017) - Ishii, Yohei; Okuma, Kazumasa; Saldana, Tiffany; Maeda, Kenji; Negishi, Nobuyuki; Manos, Jim
Abstract: In this study, atomic layer etching (ALE) of silicon nitride (SiN) using a cyclic process with monofluoromethane chemistry was investigated. Results show that an appropriate desorption time must be chosen at a specific adsorption time to achieve SiN ALE. The results also show that the infinite selectivity of SiN over Si can be achieved using the cycle process. To further understand this behavior, the adsorption and desorption effects were also studied. The results revealed a mechanism to obtain a high Si selectivity and a dominant factor that causes the Si loss. To further understand the ALE capability, we studied and compared the etched profiles and resulting surface roughness obtained by both a conventional process and an ALE process. The results show that the ALE process can achieve a high Si selectivity and a non-detectable level of Si surface damage, compared with a conventional continuous etching process.